Rabbit: More than the Magdalenian main dish in the Iberian Mediterranean region. New data from Cova de les Cendres (Alicante, Spain). (August 2020) - Real, Cristina
Graphical abstract: Highlights: Rabbit is the main prey in Magdalenian assemblages from Iberian Mediterranean region. Rabbits are an easily capture prey and provide lots of resources. Human groups process the captured rabbit to storage the meat. Correlation between the chosen processing pattern and the type of occupation. Abstract: In the Mediterranean Iberian region, rabbit has an important role in the human diet, mainly during the Final Upper Palaeolithic. The archaeological and experimental works about rabbit processing and consumption from the last years provide a wide and relevant framework. The site of Cova de les Cendres (Alicante, Spain) has a relevant role in the knowledge of the Iberian Upper Palaeolithic human subsistence, and offer a wide chronological sequence. The Magdalenian levels of Cendres provide a well-preserve archaeological assemblage of rabbit remains (ca. 90% of the total fauna) to study the human behaviour. The results show subsistence activities focus not only on meat and marrow immediate consumption, but also on skins preparation and meat storage activities. Based on these data and the framework from the area, the anthropic modifications (cut-marks, tooth-marks, fractures and fire alteration) identify on archaeological bones can specify different butchery activities. These results, however, provide more than diet information, and can be related also to different occupation pattern (function, time, seasonality) along the Magdalenian sequence of Cova de les Cendres.